Diallel Cross Application and Histomolecular Characterization: An Attempt to Develop Reference Stock of Labeo ariza - A. K. Shakur Ahammad; Neaz A. Hasan; Abul Bashar; Mohammad Mahfujul Haque; Muyassar H. Abualreesh; Md. Mehefuzul Islam; Biraj Kumar Datta; Md. Fazla Rabbi; Mohd Golam Quader Khan; Md. Samsul Alam (Biology, 2022)
The objective of the present study was to evaluate the growth performance and genetic variation in diallel crosses of Ariza labeo (Labeo ariza) originating from three geographically separated rivers (Atrai, Jamuna and Kangsha) in Bangladesh. Intra (G1K♀K♂, G2J♀J♂, and G3A♀A♂) and inter (G4K♀A♂, G5K♀J♂, G6A♀K♂, G7A♀J♂, G8J♀K♂, and G9J♀A♂) stocks were produced following diallel cross (sex ratio—1:1 and n = 48; 16 from each river). Reproductive and growth performance, muscle cellularity and genetic variation following genotyping of eight microsatellite markers (Lr1, Lr2, Lr3, Lr22, Lr24, Lr27, Lr28 and Lr29) and analysis of all crossbreeds was performed. The fertilization (95% ± 2.11%), hatching (88% ± 1.03%), and survival rates (82% ± 1.88%) of G4K♀A♂ were higher compared to other groups. With respect to length and weight gains (2.67 ± 0.4 cm and 3.39 ± 0.2 g), SGR (3.23% ± 0.20%), and heterosis (8.87% and 24.74%) G4K♀A♂ was the superior group. A higher number of hyperplastic muscle fibers, mean number of alleles (2.75) and mean observed heterozygosity (0.417) from G4K♀A♂ could be interpreted to mean that G4K♀A♂ comprise better performance efficiency compared to others and are considered for continuing the L. ariza stock improvement program.